IMPLEMENTASI LAYANAN KONSELING PADA SISWA MTs SWASTA NURUL ISLAM KECAMATAN KUALA KABUPATEN LANGKAT - Muhammad Yusuf (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2017)
Abstract: Implentation of Counseling Services at Private MTs Student Nurul Islam Kuala District Langkat.Thesis: Islamic Religious Studies Program Postgraduate of UIN North Sumatera. This study aims todescribe the counseling services that are implemented in the students of MTs Private Nurul Islam DistrictKuala Langkat District. This research uses qualitative method. Data collection was obtained by interviewtechnique, observation and documentation. The selection of resource persons is done by purposive samplingtechnique which is based on the consideration of its involvement in the implementation of counselingservice. Based on this matter, the resource persons in the research are: head of Madrasah, deputy headof madrasah, teacher of study, guardian and student. Validation of data is done by triangulation, use ofreference material.Kata Kunci: Implementasi, Layanan, Konseling